Impact resistance of steel fiber reinforced concrete in cold temperatures. (September 2021) - Zaki, Rowyda A.; AbdelAleem, Basem H.; Hassan, Assem A.A.; Colbourne, Bruce
Abstract: This study investigates the impact resistance and mechanical properties of steel fiber reinforced concrete at cold temperatures. The studied parameters include types of steel fibers (SFs) (needle fibers, single hook end, and double hook end), lengths of SFs (35 mm and 60 mm), volumes of SFs (0%, 0.35%, and 1%), coarse to sand aggregate (C/S) ratio (0.7 and 2), coarse aggregate size (10 mm and 20 mm), and cement content (300 kg/m 3 and 550 kg/m 3 ). The studied mixtures were tested under different temperatures including room temperature (20 °C), 0 °C, −10 °C, and −20 °C. The results show an improvement in the mechanical properties and impact strength at cold temperatures, with more brittle failure. The results also show that using SFs improves the mechanical properties and impact resistance of concrete at cold temperatures and reduces the low temperature brittleness of the concrete. Moreover, the effect of cold temperatures on enhancing the mechanical properties and impact resistance is more pronounced when larger volume and longer length of SFs were used.